Navigating mental health challenges in international university students: adapting to life transitions - Ansari Lari, Soroush; Zumot, Maya Salem; Fredericks, Salim (Frontiers in Psychiatry, 2025)
Change is an inevitable part of life yet navigating it can be challenging. Students transitioning from school to higher education encounter unique stressors that can significantly impact their mental health. International students face compounded difficulties as they adapt to life abroad, often for the first time, without immediate support from family and friends. This transition introduces independent living, which demands new responsibilities such as managing finances, academics, and personal well-being—tasks that are frequently underestimated. These challenges are exacerbated by cultural adjustments, language barriers, and the isolation that accompanies being far from familiar support systems. Combined, these factors contribute to heightened stress levels and increased risk of mental health concerns in this population. However, the ability to build resilience and adopt effective coping mechanisms plays a crucial role in mitigating these challenges. Among these, social support and culturally tailored university programs consistently emerge as the most effective for enhancing resilience. Further strategies such as developing strong social networks, practicing self-care, and seeking institutional support can enhance students’ ability to manage stress and adapt to their new environment. Additionally, fostering cultural competence, promoting mental health awareness, and providing tailored resources for international students can further bolster their mental well-being. Effective coping strategies identified in the literature include social support, self-compassion, culturally sensitive university programs, and mental health literacy initiatives. This paper explores the unique mental health challenges faced by international university students and highlights coping strategies aimed at promoting resilience and improving students’ capacity to thrive during this pivotal life transition.